Stress during COVID-19 pandemic: mental health condition in Indonesia (Medical Journal of Indonesia, 2020)
Pandemics have occurred throughout the decades. The last pandemic was the Spanish flu pandemic in 1918, which infected 500 million people and caused death to as many as 100 million people worldwide. At present, a similar situation is occurring as coronavirus disease 2019, caused by severe acute respiratory syndrome coronavirus 2, has infected a few million people worldwide and has been declared a pandemic by the World Health Organization in March 2020. There are various mental health responses in pandemic outbreaks. People’s thought process, behavior, and emotional response to an outbreak vary greatly according to their own backgrounds and the community that they live in. For some people, the misinformation, uncertainty, and fear of contagion may increase stress and anxiety, which can induce mass panic. Mental health education and psychological support from all stakeholders, such as the government, health professionals, and the community, may be valuable during a pandemic.